2013
DOI: 10.21608/jssae.2013.52151
|View full text |Cite
|
Sign up to set email alerts
|

Soil Management and Improvement of Salt Affected Soils

Abstract: during summer season 2011 and winter season2011/ 2012 to evaluate the effect of some soil management practices i.e., mole drain filled back with sand at two diameter 7.5 cm and 10 cm under three distances 4, 6 and 8 m individually or combined with some soil amendments application;) gypsum, sand and aluminum sulfate( on improving some physical and chemical soil properties. Also, use of the continuous leaching processes for salt removal after each rotation of leachate 25, 75, 125 and 275 days. The soil samples w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 4 publications
0
3
0
Order By: Relevance
“…As regards the reclamation efficiency in terms of improving hydraulic conductivity, various amendments proved useful effect but their combinations with mole drain may be regarded the best (Farag et al, 2013). The magnitude of hydraulic conductivity increases expected in response to gypsum applications depends on soil properties including clay content, clay mineralogy and bulk density of the soil (Reading et al, 2012).…”
Section: Nanmentioning
confidence: 99%
See 1 more Smart Citation
“…As regards the reclamation efficiency in terms of improving hydraulic conductivity, various amendments proved useful effect but their combinations with mole drain may be regarded the best (Farag et al, 2013). The magnitude of hydraulic conductivity increases expected in response to gypsum applications depends on soil properties including clay content, clay mineralogy and bulk density of the soil (Reading et al, 2012).…”
Section: Nanmentioning
confidence: 99%
“…When the soil treated with amendment combined with the mole drain, the total porosity values were increased more positively (Farag et al, 2013). Said (2002) found that at the beginning of growth season, subsoiling had a marked positive effect on soil porosity of the subsurface compacted layers.…”
Section: Introductionmentioning
confidence: 99%
“…Applied alum to saline soils and leaching the dispersive soils (the saline-sodic clay soil) once, twice, and three times has been led to a decrease in EC and ESP [18 and 19]. The reclamation of the salinesodic and clay soil by alum has been contributed to a significant decrease in EC, pH, and ESP, and thus alum is conceded as most effective amendment, followed by gypsum [20]. A study was conducted by [14] to study the effect of adding alum (aluminium sulphate) and the effect of alum with zeolite and acidified zeolite on corn.…”
Section: Introductionmentioning
confidence: 99%